Samoa : 2010 Article IV Consultation; Staff Report; Joint World Bank/IMF Debt Sustainability Analysis; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Samoa. (IMF Staff Country Reports; Country Report, 2010)
Samoa has suffered severe social and economic shocks. The outlook is challenging and subject to considerable uncertainty. Because of the tsunami's potentially severe impact on tourism, real GDP is likely to contract this financial year. The fiscal strategy to shoulder the rebuilding costs, minimize capacity risks, and ensure fiscal sustainability is appropriate. Prudent management of monetary policy and the basket peg will be critical. The Samoan economy will have to rely on the private sector for growth. Executive Directors welcome the commitment to structural reform.